In Vivo Release of Mitotic Silencing of Ribosomal Gene Transcription Does Not Give Rise to Precursor Ribosomal RNA Processing - Sirri, Valentina (The Rockefeller University Press, 2000)
Nuclear RNA transcription is repressed when eukaryotic cells enter mitosis. Here, we found that the derepression of ribosomal gene (rDNA) transcription that normally takes place in telophase may be induced in prometaphase, metaphase, and anaphase mitotic HeLa cells, and therefore appears not to be dependent on completion of mitosis. We demonstrate for the first time that in vivo inhibition of the cdc2– cyclin B kinase activity is sufficient to give rise to okadaic acid–sensitive dephosphorylation of the mitotically phosphorylated forms of components of the rDNA transcription machinery, and consequently to restore rDNA transcription in mitotic cells. These results, showing that during mitosis the rDNA transcription machinery is maintained repressed by the cdc2–cyclin B kinase activity, provide an in vivo demonstration of the cell cycle–dependent regulation of rDNA transcription. Interestingly in mitotic cells, the newly synthesized 47S precursor ribosomal RNA (pre-rRNA) is not processed into the mature rRNAs, indicating that rDNA transcription and pre-rRNA processing may be uncoupled. Moreover this suggests that inhibition of the cdc2– cyclin B kinase is not sufficient to activate the 47S pre-rRNA processing machinery and/or to induce its relocalization at the level of newly synthesized 47S pre-rRNA. This in vivo approach provides new possibilities to investigate the correlation between pre-rRNA synthesis and pre-rRNA processing when the nucleolus reforms.